Effect of level of dietary neutral detergent fibre on the ultrastructure of M cells and mucosa integrity in rabbits' appendix. Issue 1 (1st January 2021) - Zhou, Hailiang; Zhao, Xinyuan; Li, Wei; Hou, Shaopeng; Min, Xueliang; Zhu, Yanli
Abstract: Membranous (M) cells are believed to special gateways of the mucosal immune system because of sampling antigens from the gut lumen. However, little is known regarding the effect of diets on regulating M cells. So, we examined the ultrastructural characteristics of microfold (M) cells in rabbits fed different dietary fibre-to-starch ratios (I: 2.3, II: 1.9, III: 1.4, and IV: 1.0). Appendix tissues were obtained from rabbits at 52, 62, 72, and 82 d. Diet I had higher M cell area than diet IV ( p  < .01) during total experiment. Using electron microscope, we observed apparently intestinal damage and M cells apoptosis in diet I and IV compared to diet II and III ( p  < .001), except for 62d. By estimation of M cell deviations from normal structure and TNF-a mRNA expression in appendix from different diet treatments, it is apparent that degree of deviations from normal structure in diet I, IV was higher than diet II, III, except for 62 days. The appendix TNF-a mRNA levels were significantly ( p  < .01) increased in diet I, IV at 52, 62, 72, 82 days compared to diet II, III. These data elucidated that an imbalance dietary fibre-to-starch ratio induced the structural damage of M cell. Highlights: High fibre diet can increase M cell area compared to low fibre diet for rabbits. High fibre or starch diets caused rabbits' appendix mucosal damage and M cell apoptosis. High fibre or starch diets significantly increased the appendix TNF-A mRNA levels.